Thoron: Ignored and underestimated in the big shadow of radon - an example from China - Sebastian Feige; Jens Wiegand (Geofísica Internacional, 2002)
222Rn and 220Rn measurements were carried out in cave dwellings in Central China, which are dug in loess sediments. Most are constructed in a traditional style, with a floor made of loess. Inhabitants are exposed to an annual dose rate of approx. 17 mSv, mainly due to the inhalation of 220Rn decay products. Some 30 - 40 millions Chinese are estimate to be living in cave dwellings, probably the largest population group with very high radiation exposure world-wide. This contribution suggests a need to conduct further radiobiological or epidemiological investigations.